Conservative management for type A chronic thoracic aortic dissection on a patient with Marfan Syndrome, "when surgery can't be done": a case report from the rural hospital - Swempi Melchiadi Abolla; Charles Saputra (Journal of Indonesia Vascular Access, 2023)
Introduction: In aortic emergencies, aortic dissection (AD) is one of the most common. This fatal condition affected 2-3 per 100,000 people per year. Predisposing factors initiate the tear through the aorta and create the false lumen. Chronic aortic dissection is often associated with complications that make the aortic wall become weak and can lead to the rupture of the aorta. Chronic aortic dissection also can lead to an ischemic syndrome as a result of gradual impairment of distal perfusion. Emergency surgical intervention in elderly patients with type A aortic dissection is still controversial because of the high postoperative mortality and complication rate. This study aims to discuss the case of a patient who was already diagnosed with chronic aortic dissection with underlying thoracic aortic aneurysm and Marfan syndrome who gets treated conservatively Case Description: We report a case of a 54 years old female who came to the emergency department with the complaint of crushed-felt-like chest pain for the last 3 days accompanied by coughing, nausea, vomiting, and epigastric pain. The patient had been diagnosed with aortic dissection with a thoracic aortic aneurysm two months ago with a history of uncontrolled chronic hypertension and she was also diagnosed with Marfan syndrome. The patient was treated conservatively due to the high risk of mortality and morbidities for cardiac surgery. Conclusion: The decision regarding treatment options for patients with chronic aortic dissection should be considered the outcomes, mortality, and physical function. The physician needs to inform the patient and family about the condition, treatment options, long-term medical management, and the prognosis of the disease.